Narrative review of graphic humour in the media and its relationship with the construction of identity and women’s subjective wellbeing - Cárdenas Hernández, Camila Brigitte; Amezquita Bautista, Leidy Carolina (Comunicación y Género [Communication and Gender], 2021)
A narrative review of 58 studies, investigations and degree works, of qualitative or quantitative methodology, written in Colombia, the United States, Spain, Portugal and Brazil, published between 2009 and 2019 in national and international scientific journals, electronic libraries and databases, was carried out of data on graphic humor on media, particularly virtual social networks and their relationship with identity construction and subjective well-being of women. Based on that was possible to conclude the lack of studies in relation to the field of interest, especially on digital communication media, as it is the case with social networks; result that allowed to estimate the need to systematize scientific practice on this topic.
Keywords: female identity; cyberspace; subjective well-being; graphic humour